2023
DOI: 10.26599/tst.2021.9010094
|View full text |Cite
|
Sign up to set email alerts
|

Arm PSA-Certified IoT Chip Security: A Case Study

Abstract: With the large scale adoption of Internet of Things (IoT) applications in people's lives and industrial manufacturing processes, IoT security has become an important problem today. IoT security significantly relies on the security of the underlying hardware chip, which often contains critical information, such as encryption key.To understand existing IoT chip security, this study analyzes the security of an IoT security chip that has obtained an Arm Platform Security Architecture (PSA) Level 2 certification. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Figure 1 shows the behaviors of a source (on the left) and a target (on the right) as two communicating symbolic automata, focusing on the executed actions and hiding all concrete data as well as security and privilege levels. 5 Both automata synchronize their transitions with identical labels; we omitted the transition corresponding to a change of the source configuration, because it is the only unsynchronized transition.…”
Section: Modeling the Soc Behavior For Resource Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the behaviors of a source (on the left) and a target (on the right) as two communicating symbolic automata, focusing on the executed actions and hiding all concrete data as well as security and privilege levels. 5 Both automata synchronize their transitions with identical labels; we omitted the transition corresponding to a change of the source configuration, because it is the only unsynchronized transition.…”
Section: Modeling the Soc Behavior For Resource Isolationmentioning
confidence: 99%
“…Before certifying an SoC by ARM, industrial manufacturers are concerned about representing and testing resource isolation for themselves (the case study [5] showed that ARM-Certified Level 2 may leak confidential information such as AES encryption keys). Resource isolation should ensure that data contained in an IP (Intellectual Property, as are components usually called in the hardware community) protected with given security and privilege levels can only be accessed by an IP with corresponding or higher levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of Internet of Things devices are deployed in uncontrolled settings in order to collect and monitor data about connected physical or digital objects. The amount of storage capacity they have, the processing power they have, and the rates at which they can transfer data are all constrained [ 10 ]. In addition, the devices and networking protocols used by these systems are quite diverse.…”
Section: Issues With Cloud Based Aiotsmentioning
confidence: 99%
“…This implies that all devices are identified, connected, and approved by means of an architecture that is powered by a massively powerful cloud server. Alternately, the growing magnitude, complexity of network and cloud infrastructures is contributing to an increase in the cost of centralized AIoT systems [ [10] , [11] , [12] ]. An additional layer of complexity is introduced whenever there is a growing need for data to be interoperable, immutable, and verifiable when it is being traded across AIoT networks that include several parties.…”
Section: Introductionmentioning
confidence: 99%